Sequences of digestible lysine for gilts from 60 to 148 days of age - Silva Júnior, Veredino Louzada da; Donzele, Juarez Lopes; Oliveira, Rita Flávia Miranda de; Saraiva, Alysson; Silva, Francisco Carlos de Oliveira; Kill, João Luís (Ciência Rural, 2015)
The experiment was conducted to evaluate five nutritional plans based on sequences of standardized ileal digestible lysine: 0.90-0.80-0.70, 1.00-0.90-0.80, 1.10-1.00-0.90, 1.20-1.10-1.00, and 1.30-1.20-1.10% fed to gilts from 60 to 99, 129 to 100, and 130 to 148 days of age, respectively. Eighty commercial hybrid gilts, selected for lean gain, with initial weight of 23.46±0.27kg were allotted in a randomized block design, with five treatments, eight replicates, and two pigs per experimental unit. No effect (P>0.05) of the nutritional plans was verified on daily feed intake, daily weight gain and feed conversion. The nutritional plans had no influence (P>0.05) on any of the carcass traits evaluated (carcass yield, meat amount, and meat yield). The nutritional plan of 0.90-0.80-0.70% standardized ileal digestible lysine fed to gilts from 60 to 99, 100 to 129, and 130 to 148 days of age, respectively, meets the standardized ileal digestible lysine requirements of gilts from 60 to 148 days of age.

O experimento foi conduzido com o objetivo de avaliar cinco planos de nutrição baseados em sequências de lisina digestível verdadeira: 0,90-0,80-0,70; 1,00-0,90-0,80; 1,10-1,00-0,90; 1,20-1,10-1,00 e 1,30-1,20-1,10%, fornecidos dos 60 aos 99, dos 100 aos 129 e dos130 aos 148 dias de idade, respectivamente. Foram utilizadas oitenta leitoas, híbridas comerciais, selecionadas para deposição e carne, com peso inicial de 23,46±0,27kg. Os animais foram distribuídos em delineamento de blocos ao acaso, com cinco tratamentos, oito repetições e dois animais por unidade experimental. Não houve efeito (P>0,05) dos planos nutricionais no consumo de ração diário, no ganho de peso diário e na conversão alimentar. Os planos nutricionais não influenciaram (P>0,05) nenhum dos parâmetros de característica de carcaça avaliados (rendimento de carcaça quente, quantidade de carne e rendimento de carne). O plano nutricional de lisina digestível verdadeira de 0,90-0,80-0,70% fornecido dos 60 aos 99, dos 100 aos dos 129 e 130 aos 148 dias de idade, respectivamente, atende às exigências de lisina digestível verdadeira de leitoas dos 60 aos 148 dias de idade.
Keywords: Amino acid; Carcass; Performance; Pigs; Requirement; Aminoácidos; Carcaça; Desempenho; Exigência; Suínos